Digitalization as a driving force of business models of a closed-cycle economy - M. V. Rybasova; E. I. Serova (Вестник Северо-Кавказского федерального университета)
Introduction. New cyclical business models can develop at all stages of the product lifecycle. Digitalization can lead to breakthrough innovations, new business models and new ways of cooperation and, thus, accelerate the economic transition to more resource-saving and closed production systems.Goal. The study of the features of digitalization as a driving force of business models of the closed-cycle economy.Materials and methods. There is little empirical research on the stimulating role of digitalization in a closed-loop economy. To eliminate this gap, the article explores the role of digitalization in simplifying cyclical business models based on an empirical analysis of a data set of 599 Russian manufacturing firms and 296 industrial service providers.Results and discussion. While relatively few Russian firms rely on new business models to implement their resource efficiency strategy, we believe that this share is higher for companies with a strong focus on digital technologies in the manufacturing sector. This suggests that digitalization can indeed become the driving force behind the introduction of cyclical business models.Conclusion. The integration of cyclicity into business models is a key lever for the transition to a closed-loop economy. Despite the fact that it is widely recognized that digitalization causes disruptions in a wide range of areas, there is not enough literature linking this concept with the closed-loop economy and confidence-building measures as a means of contributing to disruptions in the closed-loop operation. This article examines this gap by conceptualizing cyclical disruption, which can become a key factor in accelerating the transition to a closed-loop economy. There is a wide range of DTS that can contribute to the breach of mutual responsibility and innovative ways of doing circular business discussed in this article.